Donati Graeci : learning Greek in the Renaissance - Ciccolella, Federica. (Columbia Studies in the Classical Tradition, 2008)
The starting point generally acknowledged for the revival of Greek studies in the West is 1397, when the Byzantine Manuel Chrysoloras began to teach Greek in Florence. With his Erotemata, Chrysoloras gave to Westerners a tool to learn Greek; the search for the ideal Greek textbook, however, continued even after the publication of the best Byzantine-humanist grammars. The four Greek Donati edited in this book-"Latinate" Greek grammars, based on the Latin schoolbook entitled Ianua or Donatus-belong to the many pedagogical experiments documented in manuscripts. They attest to a tradition of Greek studies that probably originated in Venice and/or Crete: a tradition certainly inferior to the Florentine scholarship in quality and circulation, but still important in the cultural history of the Renaissance.